Islamic Education and Value Analysis of Religious Moderation in Jalaluddin Rumi's Sufi Order - Muizzuddin, M.; Zaenuri, Ahmad; Anam, Saeful (Indonesian Journal of Islamic Education Studies (IJIES), 2024)
This study aimed to investigate and analyze Jalaluddin Rumi's teachings on religious moderation and Islamic education within his Sufi tradition. A qualitative method was utilized in this study, including library study, field observations, and interviews with individuals involved in Islamic education at Pesantren. The findings revealed that Jalaluddin Rumi did not explicitly discuss the concept of religious moderation. Instead, he devoted his life to propagating Sufi values and attitudes closely aligned with Islamic beliefs, mystical knowledge (marifat), and sharia as elements of religious moderation. The values of religious moderation conveyed in Rumi's works include compassion (rahmat), humility (tawadhu), excellence (ihsan), forgiveness, mutual respect, tolerance, and peace. This study, conducted at Pesantren Raudhatul Mutta'alamin in Lamongan, illustrated the significant relevance of Jalaluddin Rumi's Sufi teachings to advancing Islamic education and promoting religious moderation in Indonesia.